HUBUNGAN DISIPLIN PERKULIAHAN DENGAN HASIL BELAJAR MAHASISWA MATA KULIAH SURVEY DAN PEMETAAN 1 SEMESTER GANJIL TAHUN AKADEMIK 2013/2014 - 543-549 , Rizky Ferdian Putra (Universitas Negeri Padang, 2014)
ABSTRACT The problem in this research is the undisciplined of students in surveying and mapping class. Therefore, this research aimed to find out how much college discipline relationship with student of learning outcomes odd semester academic in 2013/2014. The type of research conducted was descriptive correlational. Population in this research are 150 students from 9 sections. Sampling using a purposive sampling with particular considerations then, the selected to be sampled are 45574 section. The data were obtained from the rubric which then analyzed using a technique Pearson Correlation with SPSS version 15.00. The results of this research revealed that the degree achievement of the course student discipline and student of learning outcomes quite enough. From the analysis result, the significant correlation discovered between disciplines count lectures with learning outcomes, and significantly rhitung 0779 alpha = 0.000> 0.05. The amount of contribution to the discipline of the course learning outcomes amounting 63.84%. Means there is a positive contribution to the discipline of the course with learning outcomes in survey and mapping. Keyword: Discipline Class, Result study, 1st Survey and Mapping Course